2007
DOI: 10.1111/j.1751-553x.2006.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based platelet reference values for an Iranian population

Abstract: There are a few reports regarding the reference range for platelet indices in the populations of Iran and its neighbouring countries, but these studies were of small sample size. This study aimed at defining platelet reference values for medical research and practice. A cross-sectional survey was performed on 19,993 young adult Iranians who participated in a compulsory pre-marriage screening programme over a 6-month period. Platelet indices were measured using an automated Technicon H2 cell counter. The platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
0
15
1
3
Order By: Relevance
“…8,10-12 PDW is used to determine the heterogeneity of platelet size. 13,14 Platelet activation can cause both morphologic and quantitative changes of platelets. PC measures the number of platelets in the blood, and PCT is a complementary analysis of PC and measures the percentage of platelets in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…8,10-12 PDW is used to determine the heterogeneity of platelet size. 13,14 Platelet activation can cause both morphologic and quantitative changes of platelets. PC measures the number of platelets in the blood, and PCT is a complementary analysis of PC and measures the percentage of platelets in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, in some non-Western populations, platelet count values between 100 and 150 ϫ 10 9 /L are frequently found in apparently healthy people. [20][21][22] The new cutoff level will also avoid inclusion of most women with pregnancy-related thrombocytopenia, a well known physiologic phenomenon not requiring specific follow-up in the absence of additional clinical features 23 (Table 1).…”
Section: Recommendationsmentioning
confidence: 99%
“…In healthy non-western populations platelet count values between 100 and 150 Â 10 9 /L are frequent. 3,4 In addition, a prospective cohort study of healthy subjects with platelet count between 100 and 150 Â 10 9 /L showed only a 6.9% 10-year probability of developing a more severe thrombocytopenia. 5 The consensus group recommended a platelet count of less than 100 Â 10 9 /L to support a diagnosis of ITP.…”
Section: Definitionmentioning
confidence: 99%